Ocena znaczenia dochodów z działalności rolniczej w dochodach gospodarstw domowych Pomorza Środkowego - Strzelecka, Agnieszka; Szafraniec-Siluta, Ewa; Zawadzka, Danuta (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The aim of the paper is formulated by describing three research tasks: a) the identification of income sources of households in Poland, and their structure, with particular emphasis on income from individual farms in the years 1996– –2010; b) the analysis of the Middle Pomerania households structure – by sources of income; c) the evaluation of the agricultural income significance in household income of Middle Pomerania. The main source of households’ income in Poland was the hired labor, social security and social assistance benefits. Agricultural activity of farms is essential in realizing of the productively farms’ function in Poland. Different situation is in the region of Middle Pomerania. Households whose main source of income are pensions determine the largest percentage of the reference population (the greater extent in the Koszalin subregion than in the Slupsk subregion), followed by a household whose main income was wage labor, then farming. During the analyzed period the household income of farmers increased, but these entities are still the socio-economic group, which achieves some of the lowest income. Therefore, the households of farmers looking for alternative sources of income, or a completely abandon the agricultural business, which is confirmed by the decreasing number of farms in Poland.